Pre- and post-merger efficiency of Islamic state-owned bank: A case study of Bank Syariah Indonesia - Hakimi, Fifi; Maf'ula, Faricha; Gultom, Rifyal Zuhdi (Universitas Islam Indonesia, 2024)
IntroductionThe increased development of Islamic banks in Indonesia is one way the government promotes state financial inclusion. On January 27, 2021, the Financial Services Authority (Otoritas Jasa Keuangan) formally granted permission for corporate mergers. Subsequently, on February 1, 2021, BRI Syariah, Bank Syariah Mandiri, and BNI Syariah, three state-owned Islamic banking companies, were officially merged to form Bank Syariah Indonesia. This study evaluates the performance efficiency of these three Islamic banks before and after the merger and compares it to other state-owned conventional banks using the Data Envelopment Analysis (DEA) approach with the BCC model framework.ObjectivesThis study aims to compare Bank Syariah Indonesia's efficiency levels before and after the merger and assesses its performance relative to other state-owned conventional banks.MethodThis research utilizes the DEA method with the BCC model to analyze quarterly financial data from March 2019 to March 2023. The inputs considered are total deposits, personal expenses, and fixed assets, whereas the outputs are financing (loans) and income.ResultsThe results indicate that Bank Syariah Indonesia is more efficient than other conventional state-owned banks after the merger. However, pre-merger, BRI Syariah and BNI Syariah ranked first in efficiency compared to conventional state-owned banks. The post-merger analysis shows a stable and high-efficiency level for Bank Syariah Indonesia despite fluctuations.ImplicationsThe findings suggest that the merger improved Bank Syariah Indonesia's performance efficiency, making it a benchmark for state-owned banks. The study highlights the importance of mergers in enhancing efficiency and suggests areas for further improvement, such as risk-mitigation strategies during economic downturns.Originality/NoveltyThis study provides additional literature on the impact of mergers on the efficiency of Islamic banks in Indonesia. It extends previous studies on Islamic bank mergers by offering insights into performance differences before and after the merger, using Bank Syariah Indonesia as a case study.